Hubungan Self-Disclosure dengan Komunikasi Interpersonal pada Mahasiswa FPK Tahun Pertama Universitas Negeri Padang - Melvino, Farid; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between self-disclosure and interpersonal communication among first-year students at the Faculty of Psychology and Health, Universitas Negeri Padang. A quantitative approach with a correlational method was employed. The sample consisted of 505 students selected through total sampling. Data were collected using two psychological scales: the self-disclosure scale developed by Setiawan (2022), based on Leung's (2002) dimensions, and the interpersonal communication scale developed by Siregar (2019), referring to DeVito’s (2011) components. The self-disclosure scale comprised 32 items, while the interpersonal communication scale consisted of 38 items. Data were analyzed using Pearson correlation with the assistance of JASP software. The results revealed a positive and significant relationship between self-disclosure and interpersonal communication. This indicates that the higher the level of students’ self-disclosure, the better their interpersonal communication skills. Conversely, low self-disclosure is associated with weaker communication abilities. These findings affirm that self-disclosure is a key factor in fostering effective communication, particularly during the initial stages of campus life adaptation.